The Effectiveness of Smart Booklet Educational Media on Foot Care Behavior in Efforts to Prevent Diabetic Food Ulcer in Type 2 Diabetes Mellitus Patients At the Limboto Health Center - Laila Revalina Madu; Ita Sulistiani Basir; Sitti Fatimah M. Arsad (Universitas Muhammadiyah Palu, 2026)
Type 2 Diabetes Mellitus is a chronic disease with one of the complications being Diabetic Foot Ulcer (DFU). Prevention of DFU depends on good foot care behaviors, but there are still many patients who have not applied it optimally. Education using SMART Booklet media is one of the promotive and preventive efforts to improve foot care behavior. This study aims to determine the effectiveness of the SMART Booklet educational media on foot care behavior in type 2 Diabetes Mellitus patients at the Limboto Health Center. This study uses a pre-experimental design with a one group pre-post test design approach. The study population was 188 patients, with a sample of 33 respondents selected using purposive sampling techniques. The research instrument used the Nottingham Assessment of Functional Foot Care (NAFF) questionnaire. Data analysis was conducted using the Wilcoxon Signed Rank Test. The results showed an improvement in foot care behavior after the intervention with a p-value = 0.000 (p < 0.05), which means that there was a significant difference before and after education. The SMART Media Booklet is said to be effective because it is designed based on the principles of Specific, Measurable, Achievable, Relevant, and Time-bound which presents foot care steps in detail, systematic, and in accordance with the patient's condition, making it easier for patients to follow the stages of treatment gradually and form habits that are carried out regularly. The presentation of structured and readable material also strengthens the consistency of the implementation of foot care in daily life.